2011
DOI: 10.1051/0004-6361/201117336
|View full text |Cite
|
Sign up to set email alerts
|

The terrestrial Planet V hypothesis as the mechanism for the origin of the late heavy bombardment

Abstract: In this study we attempt to model, with numerical simulations, the scenario for the origin of the late heavy bombardment (LHB) proposed in Chambers (2007, Icarus, 189, 386). Chambers suggested that the orbit of a fictitious sub-Mars sized embryo outside Mars became unstable and crossed a part of the asteroid belt until it was removed through ejection or collision. Chambers demonstrated that this kind of evolution can occur at the LHB time, but he did not check whether enough material could be liberated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In line with the model and results described in Sections 8 and 9, it is interesting to note that, in several other scenarios, the inclusion of additional planets during the early solar system seem to provide better results over standard models (Chambers, 2007;Ford and Chiang, 2007;Yeh and Chang, 2009;Brasser and Morbidelli, 2011;Nesvorny, 2011;Gomes and Soares, 2012). This suggests that a consistent model for the entire solar system should include not only the known terrestrial and giant planets, but also other massive planetary bodies that probably existed in large numbers at the end of planet formation.…”
Section: Discussionsupporting
confidence: 77%
“…In line with the model and results described in Sections 8 and 9, it is interesting to note that, in several other scenarios, the inclusion of additional planets during the early solar system seem to provide better results over standard models (Chambers, 2007;Ford and Chiang, 2007;Yeh and Chang, 2009;Brasser and Morbidelli, 2011;Nesvorny, 2011;Gomes and Soares, 2012). This suggests that a consistent model for the entire solar system should include not only the known terrestrial and giant planets, but also other massive planetary bodies that probably existed in large numbers at the end of planet formation.…”
Section: Discussionsupporting
confidence: 77%
“…Of course, one of the strengths of the Nice Model is that it provides a natural explanation for the Late Heavy Bombardment (LHB) seen in the lunar crater record (Gomes et al 2005), and an early instability in the outer solar system reopens the puzzle of the LHB. While other potential LHB mechanisms exist, they are either not well-developed or have not held up to additional scrutiny (e.g., Chambers 2007;Brasser & Morbidelli 2011;Minton et al 2015a). However, the Nice Model LHB mechanism may be at odds with the existence of our terrestrial planets.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the findings of Raymond et al (2009) who showed that in systems where giant planets are in slightly excited orbits, some embryos may maintain their orbits in the asteroid belt region for 200 Myr of integration. These authors also showed that it is improbable that during the formation of terrestrial planets, a Marssized embryo could have been stranded in the asteroid belt and maintained its orbit for 100 Myr (Raymond et al, 2009;Brasser et al, 2011). Such an embryo would have disturbed the orbits of other bodies in its vicinity, creating a gap in the protoplanetary disk that is not observed in the present day asteroid belt 1 .…”
Section: Formation Of Asteroid Belt Analogsmentioning
confidence: 99%